The Influence Of Service Quality And Facilities On Guest Satisfaction At The Tentrem Semarang Hotel - Caesar Ari Wibowo; Hendrajaya Hendrajaya (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This study aims to analyze and determine the effect of service quality and facilities partially and jointly on guest satisfaction at Hotel Tentrem Semarang and the most influential variable on guest satisfaction at Hotel Tentrem Semarang. The population in this study were guests or visitors at Hotel Tentrem Semarang, totaling 10,261 guests. The sampling technique in this study used accidental sampling technique. The sample of this study were guests or visitors at Hotel Tentrem Semarang as many as 99 respondents. The analysis technique used in this study is multiple linear regression analysis. The results of the study stated that service quality had a positive and significant effect on guest satisfaction at Hotel Tentrem Semarang. Meanwhile, facilities have no significant effect on guest satisfaction at Hotel Tentrem Semarang. However, service quality and facilities have a joint effect on guest satisfaction at Hotel Tentrem Semarang. Service quality is the biggest variable that influences guest satisfaction at Hotel Tentrem Semarang with a coefficient value of 0.765.